Factors affecting treatment delays among malaria patients presenting at health facilities in Guinea, 2022–2023 - Diallo, Elhadj Marouf; Kourouma, Karifa; Diakite, Nouman; Diallo, Abdourahamane; Blanquet, Marie; Toure, Abdoulaye; Gerbaud, Laurent; Camara, Alioune (Frontiers in Malaria, 2024)
Background Early identification and management of cases are key for controlling and eliminating malaria. This study aimed to assess the factors associated with the delay malaria treatment in Guinea. Methods Cross-sectional study was conducted at 60 health facilities in eight administrative regions from December 2022 to March 2023. Patients with a diagnosis of malaria through either microscopy or a rapid diagnostic test (RDT), were interviewed using a standardized questionnaire. Treatment delays were defined as seeking care 48 hours after the onset of symptoms. Logistic regression was performed to assess factors associated with treatment delay. Adjusted odds ratio (OR) and confidence interval (CI) were used to explain the associated factors. Results 3,300 malaria patients were included and the findings showed a median time of symptoms onset and access of malaria treatment was 3.04 days. Alarmingly, only 800 (24.24%) of all cases sought and received treatment within 48 hours of symptom onset. The multivariate logistic regression indicated that children under 5 years of age who attempted self-medication for fever were 4.32 times more likely to experience a delay in treatment than those who sought immediate medical care in health facilities (OR:4.32, 95% CI: 2.96–6.36). Children whose parents had no formal education were 3.05 times more likely to experience a delay in treatment (OR:3.05, 95% CI: 1.66–5.60). Moreover, when the disease was considered non-severe the first time by caregivers, OR = 1.71 (95% CI: 1.26–2.33). For those 5 years old and above, using university hospital OR = 4.01, (95% CI: 2.01–8.44), living in Forest Guinea OR = 3.14, (95% CI 1.93–5.10) and Middle Guinea OR = 1.46 (95% CI: 1.09–1.95) were more likely to experience delay treatment. Conclusions The proportion of malaria patients with treatment within 48 is low, significantly falling short of the national targets. This substantial delay in treatment was attributed to factors such the lack of formal education, self-medication practices, and failure to recognize the illness severity. These findings underscore the urgent need for NMCP to enhance awareness regarding the importance of early presentation at health facilities, with targeted interventions.